Tuning the Coordination Structure of CuNC Single Atom Catalysts for Simultaneous Electrochemical Reduction of CO2 and NO3– to Urea. Issue 32 (8th July 2022) - Leverett, Josh; Tran‐Phu, Thanh; Yuwono, Jodie A.; Kumar, Priyank; Kim, Changmin; Zhai, Qingfeng; Han, Chen; Qu, Jiangtao; Cairney, Julie; Simonov, Alexandr N.; Hocking, Rosalie K.; Dai, Liming; et al.
Abstract: Closing both the carbon and nitrogen loops is a critical venture to support the establishment of the circular, net‐zero carbon economy. Although single atom catalysts (SACs) have gained interest for the electrochemical reduction reactions of both carbon dioxide (CO2 RR) and nitrate (NO3 RR), the structure–activity relationship for Cu SAC coordination for these reactions remains unclear and should be explored such that a fundamental understanding is developed. To this end, the role of the Cu coordination structure is investigated in dictating the activity and selectivity for the CO2 RR and NO3 RR. In agreement with the density functional theory calculations, it is revealed that Cu‐N4 sites exhibit higher intrinsic activity toward the CO2 RR, whilst both Cu‐N4 and Cu‐N4− x ‐C x sites are active toward the NO3 RR. Leveraging these findings, CO2 RR and NO3 RR are coupled for the formation of urea on Cu SACs, revealing the importance of *COOH binding as a critical parameter determining the catalytic activity for urea production. To the best of the authors' knowledge, this is the first report employing SACs for electrochemical urea synthesis from CO2 RR and NO3 RR, which achieves a Faradaic efficiency of 28% for urea production with a current density of − 27 mA cm –2 at − 0.9 V versus the reversible hydrogen electrode. Abstract : Tuning the coordination structure of Cu single atom catalysts is explored for the simultaneous electrochemical conversion of CO2 and NO3 − to urea. Cu‐N4 sites achieve a Faradaic efficiency of 28% for urea, demonstrating the potential of single atom catalysts for zero‐carbon fertilizer production from waste carbon dioxide and nitrates.